Usos e percepções de comunidades do entorno de uma unidade de conservação do semiárido nordestino: instrumentos para gestão? - Silva, Thaise Sousa da (2009)
The loss of Earth´s biodiversity is a major concern for the international scientific community and megadiverse countries like Brazil are paramount for discussions about the overall situation of the planet. The Caatinga biome is probably one of the most threatened in Brazil and the implementation of Conservation Units (CU) represents a measure for protecting its natural resources and biodiversity. The Station Ecological of Seridó (ESEC-Serido) is one of the few CU in the Caatinga of Rio Grande do Norte State (NE Brazil) and interacts with several neighboring communities and settlements. However the ESEC does not integrate environmental perception feedback from the local communities in its management plan. Considering this, the present articles aims at identifying the perceptions and concepts of such communities regarding environmental issues and biodiversity as well as indicate strategies to improve the administration of this CU. In order to achieve these goals, a review of the specialized literature was carried out and a research tool based on Environmental Perception was developed in the form of structured interviews applied to the persons from communities neighboring the ESEC. These interviews were later processed through content analysis. The concepts and perceptions obtained through this analysis show that the people from the environs are aware of the main problems faced by ESEC-Seridó, as well as the strategies to address them